Analysis of pedigree data and whole‐genome sequences in 12 cattle breeds reveals extremely low within‐breed Y‐chromosome diversity. (22nd June 2021) - Escouflaire, C.; Capitan, A.
Summary: In this article, we analyzed pedigree information on males from 12 bovine breeds born in France between 2015 and 2019. We report an overall small number of paternal lineages with, for example, a minimal number of ancestors accounting for 95% of the Y‐chromosome pool of their breed ranging from only 2 to 15 individuals. Then, we mined whole‐genome sequence data from 811 sires (2 ≤ n ≤ 510 per breed) and built a median‐joining network using 1411 SNPs. Most branches were breed‐specific and in agreement with the geographic and genetic relatedness of these populations. The within‐breed haplotype diversity was lower than expected based on genealogical information, which supports the existence of major male founder effects predating pedigree recording. In addition, we observed de novo mutation events among the descendants of the same ancestors, which are of interest to define paternal sub‐lineages. Our results pave the way to future studies on the estimation of the effects of Y‐chromosome haplotypes on male reproductive performances and on the conservation of Y‐chromosome diversity.